IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA ASPEK MANAJEMEN KURIKULUM DI SEKOLAH DASAR - Anak Agung Gede Agung; Chindytia; Ni Kadek Emi Agustini; Ni Made Riska Widiastuti; Ni Putu Novita Marayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of School-Based Management (SBM) in the area of curriculum management at SD Negeri 1 Batubulan. The study employed a descriptive qualitative approach, with the school principal and teachers as the research subjects. Data collection techniques included observation, interviews, and documentation, followed by analysis through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of SBM in the aspect of curriculum management has been quite successful through collaborative planning, implementation, organization, supervision, and evaluation of the curriculum. However, there is still a lack of guidance and counseling services. Efforts undertaken by the school include empowering teachers to serve as providers of guidance and counseling services and improving coordination among educators.